The macronutrient and micronutrient (iron and manganese) content of icebergs - J. Krause; D. Carroll; J. Höfer; J. Höfer; J. Donaire; J. Donaire; E. P. Achterberg; E. Alarcón; T. Liu; L. Meire; L. Meire; K. Zhu; et al. (The Cryosphere)
Ice calved from the Antarctic and Greenland ice sheets or tidewater glaciers ultimately melts in the ocean, contributing to sea-level rise and potentially affecting marine biogeochemistry. Icebergs have been described as ocean micronutrient fertilizing agents and biological hotspots due to their potential roles as platforms for marine mammals and birds. Icebergs may be especially important fertilizing agents in the Southern Ocean, where low availability of the micronutrients iron and manganese extensively limits marine primary production. Whilst icebergs have long been described as a source of iron to the ocean, their nutrient load is poorly constrained and it is unclear if there are regional differences. Here we show that 589 ice fragments collected from calved ice in contrasting regions spanning the Antarctic Peninsula; Greenland; and smaller tidewater systems in Svalbard, Patagonia, and Iceland have similar (micro)nutrient concentrations with limited or no significant differences between regions. Icebergs are a minor or negligible source of macronutrients to the ocean with low concentrations of NOx-<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="31pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="f46d005585bd9ea185f20998258a8997"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="tc-18-5735-2024-ie00001.svg" width="31pt" height="14pt" src="tc-18-5735-2024-ie00001.png"/></svg:svg> (NO3-+NO2-<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="69pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="01457bfd8de6fde29faca3be05d2101a"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="tc-18-5735-2024-ie00002.svg" width="69pt" height="15pt" src="tc-18-5735-2024-ie00002.png"/></svg:svg>; median of 0.51 µM), PO43-<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="34pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="fa8789376663bff13723ae16a9cc5e67"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="tc-18-5735-2024-ie00003.svg" width="34pt" height="16pt" src="tc-18-5735-2024-ie00003.png"/></svg:svg> (median of 0.04 µM), and dissolved Si (dSi; median of 0.02 µM). In contrast, icebergs deliver elevated concentrations of dissolved Fe (dFe; median of 12 nM) and Mn (dMn; median of 2.6 nM). The sediment load for Antarctic ice (median of 9 mg L−1, n=144) was low compared to prior reported values for the Arctic (up to 200 g L−1). Total dissolvable Fe and Mn retained a strong relationship with the sediment load (both R2=0.43, p<0.001), whereas weaker relationships were observed for dFe (R2=0.30, p<0.001), dMn (R2=0.20, p<0.001), and dSi (R2=0.29, p<0.001). A strong correlation between total dissolvable Fe and Mn (R2=0.95, p<0.001) and a total dissolvable Mn:Fe ratio of 0.024 suggested a lithogenic origin for the majority of sediment present in ice. Dissolved Mn was present at higher dMn:dFe ratios, with fluxes from melting ice roughly equivalent to 30 % of the corresponding dFe flux. Our results suggest that NOx-<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="31pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="1ce6fcde6089ab571fd2b9ba968d58d2"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="tc-18-5735-2024-ie00004.svg" width="31pt" height="14pt" src="tc-18-5735-2024-ie00004.png"/></svg:svg> and PO43-<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="34pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="07cbafca692e8da658061fc72ff6d431"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="tc-18-5735-2024-ie00005.svg" width="34pt" height="16pt" src="tc-18-5735-2024-ie00005.png"/></svg:svg> concentrations measured in calved icebergs originate from the ice matrix. Conversely, high Fe and Mn, as well as occasionally high dSi concentrations, are associated with englacial sediment, which experiences limited biogeochemical processing prior to release into the ocean.